Bienestar psicológico en las personas mayores no dependientes y su relación con la autoestima y la autoeficacia - Mesa-Fernández, María (2019)
The aim of this study was to examine the relationship between psychological well-being, self-efficacy and self-esteem in non-dependent individuals over the age of 60. The participants included 148 seniors between 60 and 96 years of age. Data were collected through the following questionnaires: autonomy and physical and social activity scale, self-efficacy for aging scale, self-esteem scale, and the Spanish version of the wellness psychology scale. The results suggest that psychological well-being was not associated with age, but with a set of psychological factors. Psychological well-being was associated with health perception, physical and sports activities, self-efficacy, self-esteem and autonomy. The last three variables are predictors of psychological well-being. Consequently, self-efficacy and self-esteem are considered promoters of physical, psychological and social well-being, encouraging participation in physical and sports, recreational, social and cognitive activities promoting wellness and, ultimately, active aging.